Pengaruh Efektivitas Model Pembelajaran Inkuiri Terbimbing Melalui Pendekatan Kontekstual Terhadap Kemampuan Berpikir Kritis Siswa - Icha Ariskafitriani; Feri Tirtoni (STKIP Singkawang, 2025)
This Study aims to examine the effectiveness of the guided inquiry learning model through a contextual approach in enhancing the critical thinking skills of third-grade elementary school students in Civics education (PPKn). The research employed a quantitative experimental method with a Nonrandomized Pretest-Posttest Control Group Design. The sample consisted of two classes: an experimental group that used the guided inquiry model and a control group that followed conventional methods. Data were collected through pretests and posttests and analyzed using descriptive statistics, normality tests, hypothesis testing (t-test), and eta-squared analysis with SPSS version 29. The results indicated that the guided inquiry learning model significantly improved students' critical thinking skills. The average posttest score of the experimental group (91.68) was higher than that of the control group (71.27), with eta-squared values of 0.748 for the experimental group and 0.834 for the control group, indicating a strong effect. Hypothesis testing confirmed a significant difference between pretest and posttest scores (sig. < 0.05). Thus, it can be concluded that the guided inquiry model through a contextual approach is effective in enhancing students' critical thinking abilities.